Rancang Bangun Catu Daya Dan Software Dalam Apikasi Anemometer Untuk Alat Peringatan Angin Kencang - M, Noveri Lysbetti; Raudah, Aulia; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Crosswind is a very dangerous if the wind hit motorcycle. Moreover, it happened on the bridge. Strong wind warning devices are needed in order to give warning to themotorcyclist. Anemometer is a measuring instrument which can measure wind speed. The type of this anenemometer is bowl type. Rotary encoder proximity required to provide windspeed input and then it will be processed into the microcontroller ATMega 8. And ATMega will process all the data based on program in the microcontroller. The program is BASCOM AVR. From the data processing will be displayed to the LCD in the form of wind speed data. And the result of this processing will also be sent to the LEDs and buzzer alarm. The red LED will turn on when the wind speed is >22 knots as well as the buzzer sounded and thegreen LED will turn on when the wind speed is <22 knots. The strong wind warning devicesrequire a power supply. The power supply used is a line to line voltage of PLN. But sometimes, the outages caused strong winds warning device is not working. So we need abackup power supply that comes from the battery, so that strong wind warning devices can work continuously. The second power supply is controlled by a relay which is the function as a transfer switch between the power supply to be used. Main power supply output voltage of 12 V and 5 V with a maximum current of 3 A and pull out the battery charger voltage 13.20 V.Keywords: Anemometer, Bascom AVR,power supply catu daya, power supply, charger battery.